2020
DOI: 10.4108/eai.13-7-2018.164261
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual framework of Digital Health Public Emergency System: digital twins and multiparadigm simulation

Abstract: INTRODUCTION: Two major technological paradigms have been developed in recent years, digital twins and the multiparadigm simulation. In the Health Sector, the enormous potential of both approaches for the management of public health emergencies is envisioned.OBJECTIVES: This study aims to develop the conceptual framework for the development of a Digital Public Health Emergency System. METHODS: The integration of the digital twins in health with the multi-paradigm simulation for the design of a digital system o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In health care, resource allocation needs to be regulated by providing efficient services on time. Rodríguez-Aguilar et al [ 36 ] suggested a DT for a hospital that supports resource allocation (financial and human) called the Digital Health Public Emergency System (DHPES). DHPES provides efficient health services [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In health care, resource allocation needs to be regulated by providing efficient services on time. Rodríguez-Aguilar et al [ 36 ] suggested a DT for a hospital that supports resource allocation (financial and human) called the Digital Health Public Emergency System (DHPES). DHPES provides efficient health services [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rodríguez-Aguilar et al [ 36 ] suggested a DT for a hospital that supports resource allocation (financial and human) called the Digital Health Public Emergency System (DHPES). DHPES provides efficient health services [ 36 ]. The DT design seeks to generate virtual instances that emulate the real operation of the provision of highly specialized public services, including the supply of medications, supplies, devices, and equipment as well as the management of human resources and financial resources in the event of a contingency [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carvalho [99] developed a digital twin model to deal with sewage in Brazilian cities, which combined BIM and asset management.…”
Section: Water Treatmentmentioning
confidence: 99%